OVERVIEW OF THE IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH AT PT. PLN PERSERO UPDL TUNUNGAN MEDAN - Lubis, Irwansyah; Balqis, Alya Alfiyanti; Dalimunthe, Isnaini Alya Amanda; Zahara, Asni; Siregar, Nadia Safira; Siregar, Nazwa Syafira Irwani; Asti, Rahma Dwi; Artila, Tita; Wahyuni, Sri (HEARTY, 2025)
Occupational Safety and Health (K3) is an effort to create a workplace that is safe, healthy and free from environmental pollution, so as to protect and prevent workers from work accidents. PLN (Persero) UPDL Tuntungan is a State-Owned Enterprise (BUMN) agency engaged in the distribution of electrical energy and electricity services. The method used in this research is qualitative by systematically interviewing workers, managers, and HSE at PT PLN UPDL Tuntungan. The results showed that the company has run a number of structured and scheduled programs. These programs include internal and external training, provision of OHS facilities, periodic inspections, and involving workers in discussion and evaluation forums. A healthy and risk-free work environment will create a conducive working atmosphere, which in turn supports the achievement of company targets.